Building Public Trust: Public Acceptance of the Madiun City General Election Commission's Communication Strategy for the 2024 Elections - Adiakarti Farid, Muhammad Rifa'at; Rahman, Nuril Endi; Purworini, Dian (Universitas Indonesia Mandiri, 2025)
Public trust is a fundamental element in the implementation of democratic elections. The General Elections Commission (KPU), as the election organizing body, plays a strategic role in building and maintaining public trust, one of which is through effective public communication strategies. This study aims to analyze public acceptance of the communication strategies implemented by the Madiun City KPU in the 2024 Elections, and how these strategies contribute to building public trust. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews with voters, community leaders, and the Madiun City KPU, supported by observation and analysis of official KPU documents. The results show that the Madiun City KPU's communication strategies were implemented through various channels, both conventional and digital, such as face-to-face outreach, social media, and collaboration with local stakeholders. In general, these strategies were positively received by the public, particularly in increasing understanding of election stages and voter rights and obligations. However, this study also identified challenges, such as limited information reach for certain groups and differences in the level of political literacy of the community. In conclusion, the Madiun City General Elections Commission (KPU)'s communication strategy played a crucial role in building public trust in the 2024 election process, although further strengthening of inclusiveness and sustainability is still needed. This research is expected to contribute to the development of communication strategies for election organizers at the local level.